One size does not fit all: Nurturing identity needs and job satisfaction through employee benefits across gender and age - Valmori, Alessia; Reverberi, Eleonora; Manzi, Claudia (PLOS ONE, 2025)
The impact of employee benefits on workers’ identity needs was examined through an integrated framework combining social exchange theory with identity-based mechanisms. Two large-scale studies (Study 1: N = 13368, NFirms = 5; Study 2: N = 6337, NFirms = 3) investigated how the quantity (number of benefits used) and quality (satisfaction with benefits) of organizational benefits affect workers’ identity needs across four welfare categories: Work-life integration, health/safety, financial, and socio/cultural. Results consistently showed that benefits quality, rather than quantity, are more strongly associated both identity needs and job satisfaction. The impact of benefits varied according to benefit categories and demographic characteristics, suggesting the importance of considering individual differences in designing effective benefits programs.